Hubungan Kegiatan Rutinitas Keagamaan dan Pendidikan Seks Terhadap Pergaulan Bebas - Rijal Agustian; Lutfiyanti Nurhidayah; Junita Deviana; Atep Nurul Qolbi (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research was conducted against the background of the many cases of promiscuity that are happening nowadays, especially in schools in the Subang area. This is proven according to KPAI records, the type of sexual violence committed by children is the highest among other cases, there were 161 cases in 2018, 183 cases in 2019 and 44 cases in 2020. This study aims to determine the relationship between activities religious routines and sex education on promiscuity among students at SMP Negeri 1 Jalancagak. The type of research used by researchers is correlational quantitative research. The data in this study were taken using a questionnaire. The sample used was class VIII students of SMP Negeri 1 Jalancagak with a total of 35 students. The results showed that religious routine activities had a relationship to promiscuity from the results of the t-test t count 2.149 > t table 2.037 and a significance value of 0.003 <0.05 so the hypothesis was accepted, while for sex education there was no relationship to promiscuity with the results of the test- t value t count 0.102 < t table 2.037, and a significance value of 0.919 > 0.05, so the hypothesis is rejected. And based on the results of the f test that religious routine activities and sex education have a relationship to promiscuity with an F count of 4.415 greater than F table which is 3.28 and a significance value of 0.002 <0.05, so the hypothesis is accepted.